THE BROTHER'S AL-SHAFA'S PERSPECTIVE ON HUMANS - Azizah Hanum OK (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
Humans are God-created creatures who have been extensively studied by experts from various disciplines. Humans as one of God's creatures on Earth have always piqued the interest of researchers. Almost all higher education institutions research humans, their work, and the effects of that work on themselves, society, and the environment. However, despite numerous studies on humans, the essence of science, which is the result of human creation, has yet to be answered by science. This study is one of many that seek to discuss the concept of humans as defined by the Ikhwan al-Shafa. This study employs a descriptive method, taking inventory of the Brotherhood's work on humans and describing it as it is. Meanwhile, data analysis was carried out using content analysis, specifically by analyzing the meaning contained in the Ikhwan Al-overall Shafa's thinking.